Analisis Sentimen Pengguna Aplikasi OVO pada Media Sosial X menggunakan Metode Naive Bayes dan Support Vector Machine (SVM) (International Forum of Researchers and Lecturers, 2025)
The rapid development of financial technology (fintech), particularly digital wallet applications like OVO, has significantly transformed transaction patterns in society. However, issues such as server instability and unsatisfactory user experiences frequently emerge on social media platforms. This study aims to analyze user sentiments toward OVO on platform X (formerly Twitter) by comparing the performance of two machine learning algorithms: Naïve Bayes and Support Vector Machine (SVM). Data were collected through web scraping from 1,000 Indonesian-language tweets containing the keyword